Problematics Intellectual Property Rights of Music Industrialization Indonesia After The Easy Trying of Creating Work - Muhammad Habibi (Pancasila and Law Review, 2022)
Since the Government of Indonesia through President Joko Widodo ratified regulations regarding job creation (ciptaker) in 2020 which is expected to boost the Indonesian economy. However, instead of being supported, this regulation was opposed because it was projected that it would harm some people, especially in terms of Intellectual Property Rights (HaKI). Although basically the Copyright Act itself has reached the protection of intellectual property rights, but not in full. This creates a phenomenon that occurs in the music industry today which is experiencing many problems, including various copyright infringements committed by cover singers through the Youtube application. This research is a normative research using a statutory and conceptual approach. The results of this study show that the Government Regulations that were formed in relation to the ease of doing business have not been able to ensnare business actors on Youtube who plagiarize songs created through national music industry companies. The government should revise Government Regulation Number 56 of 2021 concerning Song and Music Royalties in Indonesia to ensure legal protection for songwriters in Indonesia from piracy of the works of cover singers through the Youtube application.